Magnetic and Magnetostrictive Properties of Sol-Gel-Synthesized Chromium-Substituted Cobalt Ferrite - Beera, Chandra Sekhar; Dhanalakshmi, B; Devi, D Nirmala; Vijayalakshmi, D; Mishra, Akanksha; Govindan, Ramesh; Rao, B Parvatheeswara; Shyamala, Pulipaka; Menelaou, Melita; Alanazi, Nadyah; Alodhayb, Abdullah N. (My University, 2023)
Chromium (Cr)-doped cobalt ferrite nanoparticles were synthesized using a sol-gel autocombustion method, with the chemical formula CoCrxFe2xO4. The value of x ranged from 0.00 to 0.5 in 0.1 increments. X-ray diffraction analysis confirmed the development of highly crystalline cubic spinel structures for all samples, with an average crystallite size of approximately 40 to 45 nm determined using the Scherrer equation. Pellets were prepared using a traditional ceramic method. The magnetic and magnetostrictive properties of the samples were tested using strain gauge and VSM (vibrating sample magnetometer) techniques. The results of the magnetic and magnetostrictive tests showed that the chromium-substituted cobalt ferrites exhibited higher strain derivative magnitudes than pure cobalt ferrite. These findings indicated that the introduction of chromium into the cobalt ferrite structure led to changes in the material's magnetic properties. These changes were attributed to anisotropic contributions, resulting from an increased presence of Co2+ ions at B-sites due to the chromium substitutions. In summary, this study concluded that introducing chromium into the cobalt ferrite structure caused alterations in the material's magnetic properties, which were explained by changes in the cationic arrangement within the crystal lattice. This study successfully explained these alterations using magnetization and coercivity data and the probable cationic dispersion.
Keywords: anisotropy; cobalt ferrite; crystallite size; magnetostriction; saturation magnetization